Birt-Hogg-Dubé syndrome with c.1579_1580insA variant in a Chinese family: a case report - Tang, Shijie; Wei, Chuanqi; Wang, Xiaoyu; Xiao, Min; Luo, Fengming; Chen, Lei (Frontiers in Medicine, 2023)
Birt-Hogg-Dubé (BHD) syndrome, is a rare genetic disease with heterogeneous manifestations in different populations. In this study, we reported a Chinese female BHD case and her family members with c.1579_1580insA variant in FLCN gene, who were characterized by diffused pulmonary cysts/bulla, and reviewed another five familial BHD cases in China. Based on these cases, recurrent spontaneous pneumothorax is likely to be the first symptom for BHD in Chinese patients, with particularly but not limited to c.1579_1580insA variant. Therefore, attention to the early diagnosis of BHD in China should focus on pulmonary signs, but skin or kidney lesions still can not be neglected.